Accelerated Growth Rate Induced by Neonatal High-Protein Milk Formula Is Not Supported by Increased Tissue Protein Synthesis in Low-Birth-Weight Piglets. (24th January 2012) - Jamin, Agnès; Sève, Bernard; Thibault, Jean-Noël; Floc'h, Nathalie
Abstract : Low-birth-weight neonates are routinely fed a high-protein formula to promote catch-up growth and antibiotics are usually associated to prevent infection. Yet the effects of such practices on tissue protein metabolism are unknown. Baby pigs were fed from age 2 to 7 or 28 d with high protein formula with or without amoxicillin supplementation, in parallel with normal protein formula, to determine tissue protein metabolism modifications. Feeding high protein formula increased growth rate between 2 and 28 days of age when antibiotic was administered early in the first week of life. This could be explained by the occurrence of diarrhea when piglets were fed the high protein formula alone. Higher growth rate was associated with higher feed conversion and reduced protein synthesis rate in the small intestine, muscle and carcass, whereas proteolytic enzyme activities measured in these tissues were unchanged. In conclusion, accelerated growth rate caused by high protein formula and antibiotics was not supported by increased protein synthesis in muscle and carcass.